Dose-dependent sickness behavior, abortion and inflammation induced by systemic LPS injection in pregnant mice. (27th May 2014) - Toyama, Rovana Paludo; Xikota, João Carlos; Schwarzbold, Marcelo L.; Frode, Tania Silvia; Buss, Ziliani da Silva; Nunes, Jean Costa; Funchal, Gabriela Di Giunta; Nunes, Fernanda Costa; Walz, Roger; Pires, Maria Marlene de Souza
Abstract: Objective : Clinical and experimental evidences indicate that intrauterine inflammation during pregnancy is associated to brain damage. The objective of this study is to determine the effects of lipopolysaccharide in temperature, cytokine production and sickness behavior of pregnant dams. Methods : A single i.p. injection of lipopolysaccharide (LPS) (50, 150 or 300 µg/kg) was administered on E18. Controls received isotonic saline. Body temperature was controlled before and 3 h after injections. Animals' behavior was assessed by the OF test 3 h following treatment. Animals were sacrificed for leukocyte, IL-1β and TNF-α determination. Placental tissue and abortion were also examined. Results : LPS administration elicited hypothermia. Abortion was observed in LPS 150 and 300 µg/kg. Leukocyte levels were significantly lower with LPS 300 µg/kg than in controls. LPS induced dose-dependent impairment in animals' locomotion. IL-1β serum and amniotic fluid were higher than the saline, and TNF-α serum and amniotic fluid increased when compared to controls. Placental histopathologic abnormality was not found. Conclusion : LPS induces dose-dependent sickness behavior and hypothermia in pregnant mice. Our findings suggest that the presence of inflammation may be a causative factor for premature labor and that Escherichia coli antigens modify the concentration of pro-inflammatory agents in circulatory system and intra-uterine environment.